Food inflation: A study on key determinants and price transmission processes for Malaysia - Norazman, Umi Zakiah; Khalid, Haniza; Mat Ghani, Gairuzazmi (Universiti Malaysia Sarawak, 2018)
In Malaysia, food price inflation reached its highest level at 8.8% in mid-2008 compared to overall inflation of 5.5% for the same period, mainly blamed on the spike in world commodity prices. However, recent moves by the government to rationalize food and energy subsidies have also led to higher than normal headline inflation figures and cause public concern. This study investigates the supply-side determinants of food price through a price transmission perspective. Horizontal price transmission channel relates to how trade, transportation cost, exchange rates and distances between geographical areas affect producer prices. On the other hand, vertical price transmission relates to how price changes throughout the domestic supply chain to reflect food processing and distribution costs. A vector error correction model (VECM) using monthly data from 1991 to 2013 confirms that world food commodity prices and real effective exchange rate are the primary determinants of food prices in Malaysia; whereas changes in the vertical transmission channel may have been muted by government price controls and subsidy programs or the industry’s organization. Given that world commodity price is likely to be more uncertain in the near future, understanding the dynamics of these shocks and price transmission processes will be important for future policy enhancements.